2007
DOI: 10.1248/cpb.55.1018
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Terbutaline in Pharmaceutical Formulation and Human Serum by Adsorptive Stripping Voltammetry at a Glassy Carbon Electrode

Abstract: Terbutaline sulfate (Chart 1), 2-tert-butylamino-1-(3,5-dihydroxyphenyl) ethanol hemisulfate, is an adrenergic agonist which predominantly stimulates b 2 -receptor widely used in the treatment of bronchial asthma, chronic bronchitis, emphysema and chronic obstructive pulmonary disease.1,2) The drug is given orally and/or by injection or inhalation, thus producing relaxation of bronchial smooth muscle, inhibition of the release of endogenous spasmogens, inhibition of edema caused by endogenous mediators, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Commercial Itrin tablets are produced by Kahira Pharmaceutical, Egypt. Protein‐free human serum solutions spiked with various concentrations of TRZ.HCl were prepared as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Commercial Itrin tablets are produced by Kahira Pharmaceutical, Egypt. Protein‐free human serum solutions spiked with various concentrations of TRZ.HCl were prepared as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…1,2 A literature survey revealed that various analytical methods have been reported for the estimation of TBS; they include UV spectroscopy, 3,4 voltammetry, 5,6 capillary electrophoresis, [7][8][9] chemiluminescence, [10][11][12] high performance liquid chromatography (HPLC), 1,13,14 HPLC-fluorescence detection, 15 HPLC-electrochemical detection, 16,17 HPLCchemiluminescence detection, 18 RP-liquid chromatography, 19 LC-electrochemical detection, 20 column-switching LC, 21 LC-tandem mass spectrometry, 22,23 and high-resolution GC-mass spectrometry analysis. 24 For TBS pharmacokinetic studies, the most useful analytical method is GC-mass spectrometry.…”
Section: Terbutaline Sulfate (Tbs); β-[(Tert-butylamino)methyl]-35-mentioning
confidence: 99%
“…Beltagi et al. developed a procedure based on stripping voltammetry for the determination of TER and reported a linear concentration range from 20 nM to 500 nM with a limit of detection of 6.6 nM . Yilmaz et al have also developed a procedure based on activated GCE with a linear range of 8–600 μM and a detection limit of 6 μM for terbutaline .…”
Section: Introductionmentioning
confidence: 99%